Validation of the Geriatric Sleep Questionnaire - Espirito-Santo, Helena (2021)
Objective: Assessing sleep in later life is essential for diagnosing and treating sleep problems and their consequences. We aimed to test a short questionnaire specifically designed to assess the subjective sleep quality in older people, the Geriatric Sleep Questionnaire (GSQ) Method: The GSQ was validated in a Portuguese sample of older people (N = 443; 65-100 years; M = 80.02; SD = 6.95). We analyzed reliability, factor validity, convergent validity with other theoretical similar constructs, discriminant validity with a theoretically divergent measure, and predictive power to detect sleep problems (ROC analysis). Results: A six-item version was obtained with good reliability (Cronbach's α = .79), and adequate convergent and divergent validity (p < .01). ROC analysis revealed a sensitivity of 80.0% and a specificity of 66.7% in detecting sleep problems with a cutoff point of 16 (AUC = .72). Older people in social care, low education, and living in rural areas reported worse sleep quality. Conclusion: The GSQ-6 is a brief instrument with good psychometric characteristics to assess the subjective sleep quality in older people. The GSQ-6 seems to be a valuable tool for future investigations on the relationship of sleep quality with mental health and well-being in older people.